Full- Versus Part-Day Kindergarten for Children With Disabilities: Effects on Academic and Social-Emotional Outcomes. (June 2016) - Gottfried, Michael A.; Le, Vi-Nhuan
Despite the vast body of research examining the relationship between full-day kindergarten attendance and children's outcomes, little is known about the effects of full-day kindergarten on children with disabilities (i.e., students with 1 of the 13 categories of disabilities recognized under federal law). This study fills this research void by examining whether full-day kindergarten participation predicts differences in achievement and social-emotional outcomes for children with disabilities. Using a national data set of kindergarten students from the 2010–2011 school year (ECLS-K:2011) and employing propensity matching, this study finds that relative to part-day kindergarten (PDK), full-day kindergarten (FDK) attendance is associated with higher achievement scores but also with higher frequencies of internalizing behaviors and lower incidences of self-control at the end of the kindergarten school year. The relationships between FDK attendance and outcomes varied by type of disability classification, such that significant achievement effects emerged only for children with learning and communication disorders. In addition, less time spent on child-initiated activities was associated with higher mathematics scores for children in FDK programs but not for children in PDK programs. Policy implications of the results are discussed.